Effect of numerical parameters on plastic CTOD - F.V. Antunes; R. Simoes; R. Branco; P. Prates (Fracture and Structural Integrity, 2017)
Fatigue crack growth (FCG) is associated with irreversible and non-linear processes happening at the crack tip. This explains different problems observed in the use of da/dN-?K curves, namely the inability to explain stress ratio and load history effects. The replacement of ?K by nonlinear crack tip parameters, namely the crack tip opening displacement (CTOD) is an interesting alternative. However, the determination of CTOD, using the finite element method, depends on different numerical parameters, not sufficiently studied so far. The objective here is to study the effect of these parameters on plastic CTOD, and therefore on da/dN-?CTODp curves. A transient behaviour was found at the beginning of numerical crack propagation which is linked to the formation of residual plastic wake. Therefore, a minimum number of crack increments is required to obtain stabilized values. On the other hand, the predicted ?CTODp decreases with the distance to crack tip. Close to the crack tip, sensitivity to the measured values is much higher, but it also exists at remote positions. In addition, the mesh has a relatively low influence on ?CTODp. Finally, the effect of the number of load cycles between crack increments greatly depends on material properties.